Physiological signal acquisition system - Rodriguez, G.; Infante, O.; Valenzuela, F.; Espinoza, L.; Gonzalez, C. (Revista Mexicana de Ingenieria Biomedica, 1988)
In the electrophysiological research laboratories. Normally an oscilloscope with memory, a polygraph, a stimulator, photographic processes and manual measurements are used to evaluate bioelectric signals of interest. In this work we present the design of a system, which based on a personal microcomputer (CM), captures up to 12 analog signals with 10 bits of resolution and 50 uS conversion time, manages, reports and stores them, substituting to the aforementioned team, with better features at a lower cost.